Comparative Analysis of Investment Risk and Return in Crypto Currency, LQ-45 Index Shares, Exchange Rates and Gold during the Covid-19 Pandemic - Sakina Ichsani; Neneng Susanti; Tanti Irawati Mukhlis (International Journal of Science and Society, 2023)
The purpose of this study is to determine the return and risk conditions between investments in the form of crypto currency, LQ-45 Index shares, Exchange Rates and Gold. The research period was carried out during the Covid-19 pandemic, namely from March 2020 to June 2023. The results showed that investing with Crypto Currency provided the highest return as well as risk compared to other investments studied in this study. The research results also show that there are no differences between the four investments studied. The suggestion for this research is investors should be careful in choosing the type of investment because each investment has different risks and returns and to expand the variables and research period.